Potential Association Between Microsatellite Markers on Chicken Chromosomes 6, 7 and 8 and Body Weight - Campos, R.L.R.; Ambo, M.; Rosario, M.F.; Moura, A.S.A.M.T.; Boschiero, C.; Nones, K.; Ledur, M.C.; Coutinho, L.L. (International Journal of Poultry Science, 2009)
Selective Genotyping (SG) is a strategy used to reduce the total number of markers and animals to be genotyped in order to detect QTL in a large designed population. The objective of this study was to detect potential associations between microsatellite markers on chromosomes 6, 7 and 8 (GGA6, GGA7 and GGA8) and Body Weight at 42 days (BW42), using an F2 population developed by crossing a broiler (TT) and a layer (CC) lines. Chickens were separated by sex and BW42 of 2,063 F2 offsprings was adjusted for the hatch effect. Animals that presented extreme phenotypes, i.e. the 4.5% lightest and heaviest from the normal distribution curve of phenotypes were selected within dam families, comprising 170 chickens. The means and standard deviations from the lightest and heaviest groups were 801.5 ±93.8 g and 1,328.5 ±127.8 g, respectively. Fourteen parents (TT males and CC females) and the selected 170 F2 chickens were genotyped with 25 microsatellite markers, seven on GGA6, 11 on GGA7 and seven on GGA8. Statistical analyses used the chi-square (p<0.25) to test the null hypothesis (H0) that assumed equal allele frequencies between lighter and heavier groups, indicating no association between marker and trait. On GGA6 no association was detected. On GGA7, four markers were potentially associated with BW42: ADL0279 (p=0.1976), ADL0109 (p=0.0946), ADL0315 (p=0.2343) and ADL0169 (p=0.0054). On GGA8, markers MCW0351 (p=0.1580) and ADL0154 (p=0.1741) were also associated. These associations indicate potential QTL regions, where QTL interval mapping studies should be conducted on these chromosomes to identify regions that control BW42.